The Study of Cost and Effectiveness of Magnetic Resonance Imaging (MRI) Targeted Biopsy Compared to Systemic Transrectal Ultrasound Guide Biopsy in Prostate Cancer Diagnosis - Manorom, Danai (Journal of The Department of Medical Services, 2022)
Background: At the present time, the examination of prostate cancer diagnosis with MRI is an early procedurewhen a prostate cancer is suspected. The biopsy is based on the process of magnetic resonance imaging (MRI)fusion targeted biopsy prostate (MRI-Bx), a 3D technology, along with real-time ultrasound, which encouragesdoctors to clearly see the details and location of the tumor in the prostate. This also allows doctors to accuratelyspecify where the biopsy is done without any randomization. Multiparametric Magnetic Resonance Imaging(mp-MRI) reduces the unnecessary biopsy and side effects. In Thailand, the popularity of the process has increased,but biopsy with MRI can be expensive with the cost of mp-MRI and ultrasound tools which serve the MRI fusion. Thisresearch was to study the cost-effectiveness of magnetic resonance imaging (MRI) targeted biopsy, compared withsystemic transrectal ultrasound-guided biopsy (TRUS-Bx) in prostate cancer diagnosis. Objective: To study cost andeffectiveness of magnetic resonance imaging (MRI) targeted biopsy, compared with systemic transrectal ultrasoundguided biopsy in prostate cancer diagnosis. Method: This was a retrospective study of people at risk of prostatecancer examined by MRI fusion biopsy prostate and systemic TRUS-Bx by calculating the cost of MRI targeted biopsyand its effectiveness in reducing false negative results. The results were then compared with systemic transrectalultrasound-guided biopsy. Result: There was an extra cost for MRI fusion biopsy and the incremental cost effectivenessratio was 616.69 Baht per a natural unit increased of the clinical outcome of interest when compared with systemictransrectal ultrasound-guided biopsy. Conclusion: The prostate cancer diagnosis with MRI fusion biopsy prostatewas more cost-effective when compared with systemic transrectal ultrasound-guided biopsy. The TRUS-Bx patientscan be at risks for the side effects caused by unnecessary biopsy.